A Neo-Nixon Doctrine for the Indian Ocean: helping states help themselves - Ladwig, WC (Routledge, 2012)
In recent years the Indian Ocean has received significant attention from the defence-intellectual community in the United States. However, the actual strategic importance of the region to US interests is less clear. In an environment of fiscal austerity, if commitments abroad are not firmly linked to interests, any significant involvement in a region of secondary concern could contribute to ‘imperial overstretch’. The ‘Neo-Nixon Doctrine’ outlined here calibrates American interests and regional commitments by devolving primary responsibility for regional security to the major democratic powers in the Indian Ocean, whom the US would bolster with aid and advice.